Dysregulation of the TCF4 Isoform in Corneal Endothelial Cells of Patients With Fuchs Endothelial Corneal Dystrophy - Honda, Tetsuro; Nakagawa, Tatsuya; Yuasa, Taichi; Tokuda, Yuichi; Nakano, Masakazu; Tashiro, Kei; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Yamamoto, Koji; Koizumi, Noriko; Okumura, Naoki (Investigative ophthalmology & visual science, 2024)
This study evaluated the dysregulation of TCF4 isoforms and differential exon usage (DEU) in corneal endothelial cells (CECs) of Fuchs endothelial corneal dystrophy (FECD) with or without trinucleotide repeat (TNR) expansion in the intron region of the TCF4 gene. Three RNA-Seq datasets of CECs (our own and two other previously published datasets) derived from non-FECD control and FECD subjects were analyzed to identify TCF4 isoforms and DEU events dysregulated in FECD by comparing control subjects to those with FECD with TNR expansion and FECD without TNR expansion. Our RNA-Seq data demonstrated upregulation of three TCF4 isoforms and downregulation of two isoforms in FECD without TNR expansion compared to the controls. In FECD with TNR expansion, one isoform was upregulated and one isoform was downregulated compared to the control. Additional analysis using two other datasets identified that the TCF4-277 isoform was upregulated in common in all three datasets in FECD with TNR expansion, whereas no isoform was dysregulated in FECD without TNR expansion. DEU analysis showed that one exon (E174) upstream of the TNR, which only encompassed TCF4-277, was upregulated in common in all three datasets, whereas eight exons downstream of the TNR were downregulated in common in all three datasets in FECD with TNR expansion. This study identified TCF4-277 as a dysregulated isoform in FECD with TNR expansion, suggesting a potential contribution of TCF4-277 to FECD pathophysiology.